Centrifugally manufactured hollow concrete‐filled steel tubular columns - Kuranovas, Artiomas; Kvedaras, Audronis Kazimieras (Journal of Civil Engineering and Management, 2007)
Hollow concrete‐filled steel tubular elements (H‐CFSTs) represent a type of composite steel‐concrete elements. These elements are usually produced by spinning. During this process wet concrete mix in the steel tube is displaced and compacted by centrifugal force and the concrete core so formed achieves better physical and mechanical properties in comparison with other compaction methods. These improvements are related to concrete density, Young's modulus, Poisson’ s ratio, compressive strength, deformability as well as to a more uniform distribution of fine and coarse aggregates and binding particles along the thickness of the hollow concrete core formed by multi‐layering centrifugation process. The peculiarities of the spinning process, recommendations for proportioning the components for the specimens manufacture, spinning time needed for displacement and compaction of concrete mix, preparation of specimens for testing and testing methods used are presented in this paper.Tuščiavidurių betonšerdžių plieninių vamzdinių strypų gamybos technologija ir pranašumaiSantrauka. Tuščiaviduriai betonšerdžiai plieniniai vamzdžiai (TBPV) yra vienas iš kompozitinių konstrukcijų tipų. Tokie elementai dažniausiai gaminami centrifugavimo būdu, kai betono skiedinys įpilamas į plieninį vamzdį ir tankinamas centrifuguojant, dėl to betonas įgyja geresnių fizinių ir mechaninių savybių lyginant su plačiau naudojamais tankinimo metodais. Šios savybės yra tankis, tamprumo modulis, Puasono koeficientas, gniuždomasis stipris, deformacijos, skiedinio užpildo pasiskirstymo vienodumas per gaminio storį. Šiame straipsnyje yra pateikiami centrifugavimo proceso ypatumai, betono skiedinio komponentų kiekio, proporcijų nustatymo, jų savybių, centrifugavimo laiko parinkimo, bandymo eigos ir bandymo metodų rekomendacijos.Reikšminiai žodžiai: kompozitinės konstrukcijos, tuščiaviduriai betonšerdžiai plieniniai vamzdžiai, daugiasluoksnės šerdys, centrifugavimas, gamyba, technologija.First Published Online: 14 Oct 2010